Power‐scaling properties of apertured microchip vertical external‐cavity surface‐emitting lasers. Issue 2 (1st January 2013) - Vetter, S.L.; Zhang, Y.; Gu, E.; Dawson, M.D.; Calvez, S.
Abstract : Presented is the power‐scaling characteristics of microchip vertical external‐cavity surface‐emitting lasers which include grating apertures for mode selection. Multi‐Watt multi‐lateral‐mode emission at a wavelength of 1060 nm is obtained with sub‐linear increase in maximum output power with aperture‐size. It is also shown that the polarisation is only set by the grating lines for high‐order modes which interact sufficiently with the grating.